1998
DOI: 10.1080/09064709809362400
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of broiler diets with retinol acetate, ß‐carotene or canthaxanthin: Effect on vitamin status and oxidative status of broilersin vivoand on meat stability

Abstract: Supplementation of broiler diets with retinol accetate, ß-carotene or canthaxanthin: effect on vitamin status and oxidative status of broilers in vivo and on meat stability.The oxidative status of live chickens and of the chicken meat was evaluated for 5 groups of broilers fed a diet optimized with respect to all nutrients and energy content and rich in unsaturated fatty acids from rapeseed and soybean oil. The six diets varied in dietary content of ß-carotene (5.1 or 10.2 mg kg -1 diet), canthaxanthin (2.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…However, both Ackert et al (1931) and Dubinský et al (1975) utilized natural or semi-synthetic diets which were more deficient in vitamin A than those utilized in this study; and which caused pathognomonic symptoms of vitamin A deficiency or mortality in infected chickens. Further evidence of the importance of vitamin A in host resistance to A. galli was produced by Leutskaya et al (1993) who found that supplementation of diet with orally administered vitamin A (2,500 to 5,000 IU per bird) reduced A. galli's establishment rate by 40 to 78 % in adult chickens fed balanced diets. Higher doses (10,000 to 50,000 IU vitamin A per bird) yielded worm burdens in which 70 to 100 % of the female worms were stunted and immature with a reduced male-female ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both Ackert et al (1931) and Dubinský et al (1975) utilized natural or semi-synthetic diets which were more deficient in vitamin A than those utilized in this study; and which caused pathognomonic symptoms of vitamin A deficiency or mortality in infected chickens. Further evidence of the importance of vitamin A in host resistance to A. galli was produced by Leutskaya et al (1993) who found that supplementation of diet with orally administered vitamin A (2,500 to 5,000 IU per bird) reduced A. galli's establishment rate by 40 to 78 % in adult chickens fed balanced diets. Higher doses (10,000 to 50,000 IU vitamin A per bird) yielded worm burdens in which 70 to 100 % of the female worms were stunted and immature with a reduced male-female ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A analysis Vitamin A in liver was analysed according to the procedure described by Jensen et al (1998). To liver samples (approximately 3 g) 96 % v/v ethanol was added as twice the amount (w/w).…”
Section: Parasitological Examinationmentioning
confidence: 99%
“…The FA C17:0 was used as external standard. Fat-soluble vitamins were extracted and analyzed by HPLC as described by Jensen and Nielsen (1996) and Jensen et al (1998). A PerkinElmer HS-5-Silica column (4.0 × 125 mm; Waltham, MA) was used for analyses of α-tocopherol and retinol and a Supelco amino column (4.6 × 250 mm; Sigma-Aldrich) was used for analysis of β-carotene.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Jensen et al (1998) supplemented chickens diets with 2 mg canthaxanthin/kg (from day 11 to day 42) and found no effects on fatty acid composition of thigh and breast muscle or on the oxidative stability (measured by thiobarbituric acid-reactive substances (TBARS)) of these tissues at slaughter, after chill storage for 14 days or frozen storage for 10 months. Similarly, Woodall et al (1996) did not observe an effect on the oxidative stability of breast muscle after supplementing diets with 100 mg/kg canthaxanthin.…”
Section: 3mentioning
confidence: 99%